2009
DOI: 10.1111/j.1471-0528.2009.02162.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphovascular space involvement in early stage well‐differentiated endometrial cancer is associated with increased mortality

Abstract: Objective To study the relationship between lymphovascular space involvement (LVSI) in stage 1a or 1b well-differentiated endometrial cancer and survival.Design Retrospective study consisting of a search of an oncology database to identify women with endometrial cancer between January 1990 and December 2004.Setting Tertiary referral centre, Dublin, Ireland.Sample Women who had well-differentiated stage 1a or 1b endometrial cancer.Methods During the period 1990-2004, 226 patients with endometrial cancer were tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 33 publications
4
31
0
2
Order By: Relevance
“…Lymphovascular space invasion has been defined as the presence of viable tumor cells in endothelial-lined channels, outside the bulk of the invasive tumor 11. There is increasing evidence to suggest that the presence of lymphovascular space invasion as detected by hematoxylin and eosin significantly and independently increases the risk of recurrence, even in patients with endometrial cancer surgicopathologically confined to the uterus 12–14.…”
Section: Introductionmentioning
confidence: 99%
“…Lymphovascular space invasion has been defined as the presence of viable tumor cells in endothelial-lined channels, outside the bulk of the invasive tumor 11. There is increasing evidence to suggest that the presence of lymphovascular space invasion as detected by hematoxylin and eosin significantly and independently increases the risk of recurrence, even in patients with endometrial cancer surgicopathologically confined to the uterus 12–14.…”
Section: Introductionmentioning
confidence: 99%
“…20,25,29,30 So it should be observed when possible to identify a risk group in which lymphadenectomy and/or adjuvant therapy are beneficial. 19 Although the new FIGO 2009 staging classification for EC does not include the LVSI as a prognostic indicator of stage III disease, 31 most respondents felt that the LVSI should be considered in staging or at least reported as a tumor clinicopathological feature. The Gynecologic Oncology Group (GOG) includes LVSI as a risk factor for the stratification of intermediaterisk EC into high-and low-risk subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…31 There is low incidence of positive LVSI in early invasive stage, well-differentiated histology, and tumors measuring less than 2 cm, 24 whereas deep myometrial invasion (MI) and poorly differentiated tumors are statistically significantly associated with LVSI. 21,24,31 In Jorge et al 25 study, the estimated risk of nodal metastases was 21% in positive LVSI, compared with 2.1% (P G 0.0001) in negative LVSI. In Post-Operative Radiation Therapy in Endometrial Cancer 1 trial, LVSI was found in 5% of total patients and in 17% of patients with deep MI or grade 3 tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Also, both EG1-HGSC and EG1-LGSC had a higher rate of lymphovascular invasion than pure-type EG1. In previous reports, LVSI was a risk factor of the mortality in EG1 [3,5] . These results suggested that EG1-SC was a more aggressive histological subtype compared to pure-type EG1.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent reports, the incidence of grade 1 endometrioid carcinoma (EG1) at stage IA was highest (31.7%) among all ECs, and the 5-year survival rate of EG1 in stage IA ranges from 92.3 to 93.7% [3] . In addition, retrospective studies analyzing EG1 at 2009 FIGO stage IA demonstrated that the rates of recurrence ranged from 5 to 12%, and that the sites of recurrence were vaginal cuff, pelvic wall, and liver [4,5] . Most of these cases had good prognoses; however, predictive markers for recurrence or survival are not determined.…”
Section: Introductionmentioning
confidence: 99%